Enhancing Computational Thinking Through Case-Based Object-Oriented Programming: A Study Among Informatics Students - Rahmadona Safitri; Hansi Efendi; Resmi Darni; Waskito Waskito; Denny Kurniadi (Universitas Pendidikan Ganesha, 2025)
The teaching of Object-Oriented Programming (OOP) in undergraduate informatics programs often remains procedural in nature and provides limited opportunities for developing computational thinking and real-world problem-solving skills. This condition contributes to a mismatch between graduates’ competencies and industry demands in the era of Industrial Revolution 5.0. This study aims to evaluate the effectiveness of a Case-Based Object-Oriented Programming approach integrated with Computational Thinking Skills (CTS) in improving students’ learning outcomes and problem-solving abilities. Employing a quasi-experimental one-group pretest–posttest design, the study involved 20 fifth-semester Informatics Engineering students enrolled in an Object-Oriented Programming course at a private university in Indonesia, selected through purposive sampling. Data were collected using a written CTS test, a performance rubric for real-world case projects, and scores from the Midterm and Final Examinations. Data analysis included the Shapiro–Wilk normality test, Wilcoxon Signed Rank Test to compare pretest and posttest scores, and Spearman’s Rho correlation to examine relationships among variables. The findings indicate a significant improvement in OOP learning outcomes between the midterm and final examinations, alongside a very strong correlation between CTS components and learning performance, with abstraction and decomposition contributing the most. The study concludes that integrating CTS within case-based OOP instruction is effective in enhancing students’ computational thinking and academic achievement. The results highlight the need for instructors to adopt case-based pedagogical approaches and CTS-oriented assessment instruments to better prepare students for the challenges of Industry 5.0.